Photovoltaic tin paste, preparation method thereof and solar cell
By replacing part of the silver paste with photovoltaic tin paste in photovoltaic cells, the problems of high silver consumption and poor welding caused by multi-main gate technology are solved, and the effect of reducing costs and improving welding quality is achieved.
Patent Information
- Application Number
- CN202410586696.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-05-11
AI Technical Summary
Multi-main gate technology in photovoltaic cells leads to high silver consumption of main gates and poor welding, which increases component costs.
A photovoltaic tin slurry containing lead-free alloy tin powder and flux is used to replace part of the main gate silver paste, and by printing and curing on the screen, a tin slurry layer firmly bonded to the silver gate is formed.
Reduces the consumption of silver paste, improves welding yield, reduces component costs, and achieves conductivity and improves welding effects without cleaning.
Smart Images

Figure CN118335384B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic cells, and in particular to a photovoltaic tin paste, a preparation method thereof and a solar cell. Background Art
[0002] Photovoltaic technology is developing rapidly, and the annual growth rate of solar cell production capacity has maintained more than 25% in recent years. At present, the photovoltaic cell process has rapidly shifted from the PERC process to the TOPCon process, and the conversion efficiency has rapidly increased from more than 23% to more than 26%, greatly improving the power of cells and components.
[0003] The increase in TOPCon cell power also increases the electrical loss of the grid lines of the cell, indirectly causing a loss of some module power. In order to reduce the electrical loss of the grid lines and further increase the module power, the number of main grids of photovoltaic cells has increased from the initial 5 to the current 20, and there is a trend of continued increase in the future. The increase in main grid lines will lead to an increase in main grid slurry. Currently, the main grid slurry mainly uses silver paste, which has been rising in price recently, causing the cost of the cell to further increase. A low-cost slurry is needed to replace the silver paste to reduce the consumption of silver paste and reduce costs.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a photovoltaic tin paste, a preparation method thereof and a solar cell. The present invention mainly solves the following problems: At present, photovoltaic cells use SMBB (multi-busbar) technology to reduce the grid line electrical loss of the cell and the module to achieve the purpose of reducing power loss, resulting in the problem that the multi-busbar is generally more than 15 busbars, and the multi-busbar technology causes high silver consumption of the busbar and many poor welding of the module. The photovoltaic tin paste replaces part of the busbar silver paste to achieve the purpose of reducing silver consumption. At the same time, the tin paste is simpler for welding and improves the welding yield.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] In a first aspect, the present invention provides a photovoltaic tin paste, which comprises, by weight: 85 to 90 parts of lead-free alloy tin powder and 10 to 15 parts of flux;
[0008] Wherein, the soldering flux comprises: organic solvent, organic acid, thixotropic agent, corrosion inhibitor, surfactant and modified rosin.
[0009] In the present invention, the components in the photovoltaic tin paste cooperate with each other under a certain ratio to have a synergistic effect, so as to achieve the purpose of reducing the silver paste consumption of photovoltaic cells. At the same time, the tin paste is simpler for welding and improves the welding yield. The tin paste of the present invention can be directly printed on the screen and covered on the surface of the bottom silver paste. After curing, the tin paste layer and the silver grid are firmly combined together without the need for cleaning. It can not only play a conductive role, but also improve the welding yield of the component end.
[0010] In the photovoltaic tin paste, the content of the lead-free alloy tin powder is 85 to 90 parts, for example, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, etc.
[0011] In the photovoltaic tin paste, the content of the soldering flux is 10 to 15 parts, for example, it can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.
[0012] Preferably, the lead-free tin alloy powder comprises, by mass percentage, 0-3.0% silver, 0.5-2.0% copper, and the balance tin.
[0013] Taking the total mass of the lead-free alloy tin powder as 100%, the silver content is 0-3.0%, for example, it can be 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.4%, 2.6%, 2.8%, 3.0%, etc.
[0014] Taking the total mass of the lead-free alloy tin powder as 100%, the copper content is 0.5-2.0%, for example, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, etc.
[0015] In the present invention, the lead-free alloy tin powder is added with a certain proportion of silver and copper, so that the prepared solder paste has good mechanical strength and solderability. The solidified tin paste layer can be firmly combined with the silver grid to play a conductive role and further improve the soldering yield of the component end.
[0016] Preferably, the soldering flux comprises, by mass percentage, 30-50% of an organic solvent, 1.0-2.0% of an organic acid, 0.5-2.5% of a thixotropic agent, 0.8-1.5% of a corrosion inhibitor, 1.0-3.0% of a surfactant, and the remainder is modified rosin.
[0017] Taking the total mass of the soldering flux as 100%, the content of the organic solvent is 30-50%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, etc.
[0018] Based on the total mass of the soldering flux being 100%, the content of the organic acid is 1.0-2.0%, for example, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, etc.
[0019] Taking the total mass of the flux as 100%, the content of the thixotropic agent is 0.5-2.5%, for example, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, etc.
[0020] Taking the total mass of the soldering flux as 100%, the content of the corrosion inhibitor is 0.8-1.5%, for example, 0.8%, 1.0%, 1.2%, 1.4%, 1.5%, etc.
[0021] Taking the total mass of the soldering flux as 100%, the content of the surfactant is 1.0-3.0%, for example, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, etc.
[0022] In the present invention, the soldering flux is composed of an organic solvent, an organic acid, a thixotropic agent, a corrosion inhibitor, a surfactant and a modified rosin in a specific proportion. The components cooperate with each other and synergistically enhance the effect, which can further improve the fluidity, spreading rate and solderability of the soldering flux, so that there is less residue after welding, less corrosiveness, and no need for cleaning after curing, thereby further improving the soldering yield of the components, ensuring a more firm combination of the tin paste and the silver grid, and reducing the proportion of cold solder joints.
[0023] Preferably, the organic solvent is selected from any one or a combination of at least two of propylene glycol, diethylene glycol monobutyl ether, ethylene glycol methyl ether, isopropanol, methyl silicate, ethylene glycol or dodecyl alcohol.
[0024] Preferably, the organic acid is selected from any one of succinic acid, sebacic acid, malic acid, salicylic acid, phthalic acid, dodecanoic acid, tetradecanoic acid or hexadecanoic acid, or a combination of at least two thereof.
[0025] Preferably, the thixotropic agent is selected from any one of hydrogenated castor oil, polyamide wax, organic bentonite or silicon dioxide, or a combination of at least two thereof.
[0026] Preferably, the corrosion inhibitor is selected from any one of hydroquinone, benzotriazole or tolyltriazole, or a combination of at least two thereof.
[0027] Preferably, the surfactant is selected from any one or a combination of at least two of nonylphenol polyoxyethylene (10) ether, octylphenol polyoxyethylene (10) ether, hexadecylamine or polyoxyethylene fatty acid ester.
[0028] Preferably, the modified rosin comprises any one or a combination of at least two of the following compounds:
[0029]
[0030] In a second aspect, the present invention provides a method for preparing the photovoltaic tin paste as described in the first aspect, the preparation method comprising the following steps:
[0031] The organic solvent, organic acid and modified rosin are mixed for the first time, and then a thixotropic agent, a corrosion inhibitor and a surfactant are added for the second mixing to obtain the soldering flux;
[0032] The lead-free alloy tin powder and the soldering flux are mixed for a third time to obtain the photovoltaic tin paste.
[0033] Preferably, the temperature of the first mixing is 80-120°C, for example, it may be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 115°C, 120°C, etc.
[0034] Preferably, the stirring speed of the first mixing is 30-40 rpm, for example, 30 rpm, 32 rpm, 34 rpm, 36 rpm, 38 rpm, 40 rpm, etc.
[0035] Preferably, the first mixing time is 5 to 10 minutes, for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, etc.
[0036] Preferably, the temperature of the second mixing is 30-50°C, for example, it may be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, etc.
[0037] Preferably, the stirring speed of the second mixing is 20-25 rpm, for example, it can be 20 rpm, 21 rpm, 22 rpm, 23 rpm, 24 rpm, 25 rpm, etc.
[0038] Preferably, the second mixing time is 20 to 40 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, etc.
[0039] Preferably, the temperature of the third mixing is 30-50°C, for example, it can be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, etc.
[0040] Preferably, the stirring speed of the third mixing is 10-15 rpm, for example, it can be 10 rpm, 11 rpm, 12 rpm, 13 rpm, 14 rpm, 15 rpm, etc.
[0041] Preferably, the third mixing time is 30 to 60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0042] Preferably, the third mixing is performed in the presence of a protective atmosphere.
[0043] Preferably, the protective atmosphere is nitrogen.
[0044] In a third aspect, the present invention provides a solar cell, wherein the main grid of the solar cell comprises a silver grid line and a tin paste layer;
[0045] Wherein, the tin grid lines are formed by solidifying the photovoltaic tin paste as described in the first aspect.
[0046] In the present invention, the tin paste can be directly printed on the screen, covering the surface of the bottom silver paste, and baked at 200-250°C for 20-60s. After curing, the tin paste layer and the silver grid line can be firmly combined together without the need for cleaning, which can not only play a conductive role, but also improve the soldering yield of the component end.
[0047] Furthermore, the solar cell comprises a P-type PREC cell or an N-type Topcon cell.
[0048] Preferably, the height of the silver grid lines is 1-3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, etc.
[0049] Preferably, the height of the tin paste layer is 7 to 14 μm, for example, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, etc.
[0050] Preferably, the total height of the main grid is 10-15 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.
[0051] In a fourth aspect, the present invention provides a method for preparing a P-type PREC cell, the method for preparing a P-type PREC cell comprising the following steps:
[0052] Print back silver and back aluminum on the back of the blue film and dry it;
[0053] Print the silver main grid on the front of the blue film and sinter it;
[0054] The photovoltaic tin paste as described in the first aspect is printed on the surface of the back silver and the silver main grid respectively, and then cured to obtain the P-type PREC cell.
[0055] Preferably, the front side of the blue film includes printed silver main grid and printed silver secondary grid in addition to the printed silver main grid.
[0056] Preferably, in the preparation of the P-type PREC cell, the sintering temperature after printing the silver main grid on the front side is 300-800°C, for example, it can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.
[0057] In the present invention, a silver main grid is printed on the front side of the blue film, and sintered at a high temperature of 300-800° C. so that the silver paste and silicon form an ohmic contact.
[0058] Preferably, in the preparation of the P-type PREC battery cell, the curing treatment is baking, and the baking temperature is 200-300°C, for example, it can be 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, etc.; the baking time is 20-60s, for example, it can be 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s, etc.
[0059] It should be noted that the assembly is made after the cell is tested and graded. The assembly end is normally welded to the main grid line with a soldering strip (tin-coated copper strip). The silver of the main grid and the soldering strip have a certain proportion of false soldering. The main grid surface of the cell made by the present invention has a layer of tin paste. During welding, the tin on the main grid and the tin on the soldering strip are dissolved and mixed together. After cooling, they can be better combined, reducing the proportion of false soldering.
[0060] In a fifth aspect, the present invention provides a method for preparing an N-type Topcon cell, the method for preparing an N-type Topcon cell comprising the following steps:
[0061] Print silver main grids on the front and back of the blue film and sinter them;
[0062] The photovoltaic tin paste as described in the first aspect is printed on the surfaces of the silver main grids on the front and back sides respectively, and then cured to obtain the N-type Topcon cell.
[0063] Preferably, in the preparation of the N-type Topcon cell, the sintering temperature after printing the silver main grid on the front and back sides is 300-800°C, for example, it can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.
[0064] Preferably, in the preparation of the N-type Topcon battery cell, the curing treatment is baking, and the baking temperature is 200-300°C, for example, it can be 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, etc.; the baking time is 20-60s, for example, it can be 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s, etc.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] (1) The components in the photovoltaic tin paste of the present invention cooperate with each other in a certain ratio to achieve the purpose of reducing the silver paste consumption of photovoltaic cells.
[0067] (2) The tin paste of the present invention can be directly printed on a screen and covered on the surface of the bottom silver paste. After curing, the tin paste layer and the silver grid are firmly combined together without the need for cleaning. It can not only play a conductive role, but also improve the soldering yield of the component end. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0069] Figure 1 It is a schematic diagram of the structure of the P-type PREC battery cell described in the present invention.
[0070] Among them, 1 is a P-type silicon substrate, 2 is a phosphorus diffusion layer, 3 is a front silicon nitride layer, 4 is a back aluminum oxide layer, 5 is a back silicon nitride layer, 6 is back aluminum, 7 is back silver, 8 is a silver main gate, 9 is a back tin paste layer, 10 is a front tin paste layer, and 11 is a laser groove.
[0071] Figure 2 It is a schematic diagram of the structure of the N-type Topcon cell described in the present invention.
[0072] Among them, 11 is an N-type silicon substrate, 12 is a boron diffusion layer, 13 is an aluminum oxide layer, 14 is a front silicon nitride layer, 15 is a tunneling oxide layer, 16 is a poly layer, 17 is a back silicon nitride layer, 18 is a front silver main gate, 110 is a front tin paste layer, 19 is a back silver main gate, and 111 is a back tin paste layer. DETAILED DESCRIPTION
[0073] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0074] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0075] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0076] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0077] Example 1
[0078] This embodiment provides a photovoltaic tin paste, which is composed of the following components by mass percentage: 88% lead-free alloy tin powder and 12% soldering flux;
[0079] Wherein, the lead-free alloy tin powder is composed of the following components by mass percentage: 3% silver, 0.5% copper, and 96.5% tin;
[0080] Wherein, the soldering flux is composed of the following components by mass percentage:
[0081]
[0082] The preparation method of the photovoltaic tin paste comprises the following steps:
[0083] S1. Place an organic solvent, rosin resin, organic acid activator and organic solvent in a reaction kettle with a heating device, heat to 100° C., and stir at a speed of 35 rpm for 8 min to make them uniform; add a thixotropic agent, a corrosion inhibitor and a surfactant to the above mixture, and after dissolving, stir at 35° C. and a speed of 20 rpm for 30 min, let it stand and cool, and after cooling for 24 hours, obtain the soldering flux;
[0084] S2. Mix the tin powder and the soldering flux, place in a mixer, evacuate, flush with nitrogen, and then stir at 35° C. and 12 rpm for 50 min to obtain the photovoltaic tin paste.
[0085] Example 2
[0086] This embodiment provides a photovoltaic tin paste, which is composed of the following components by mass percentage: 85% lead-free alloy tin powder and 15% soldering flux;
[0087] Wherein, the lead-free alloy tin powder is composed of the following components by mass percentage: 1% silver, 1% copper, and 98% tin;
[0088] Wherein, the soldering flux is composed of the following components by mass percentage:
[0089]
[0090] The preparation method of the photovoltaic tin paste comprises the following steps:
[0091] S1. Place an organic solvent, rosin resin, organic acid activator and organic solvent in a reaction kettle with a heating device, heat to 100° C., and stir at a speed of 35 rpm for 8 min to make them uniform; add a thixotropic agent, a corrosion inhibitor and a surfactant to the above mixture, and after dissolving, stir at 35° C. and a speed of 20 rpm for 30 min, let it stand and cool, and after cooling for 24 hours, obtain the soldering flux;
[0092] S2. Mix the tin powder and the soldering flux, place in a mixer, evacuate, flush with nitrogen, and then stir at 35° C. and 12 rpm for 50 min to obtain the photovoltaic tin paste.
[0093] Example 3
[0094] This embodiment provides a photovoltaic tin paste, which is composed of the following components by mass percentage: 90% lead-free alloy tin powder and 10% soldering flux;
[0095] Wherein, the lead-free alloy tin powder is composed of the following components by mass percentage: 1.5% silver, 0.5% copper, and 98% tin;
[0096] Wherein, the soldering flux is composed of the following components by mass percentage:
[0097]
[0098] The preparation method of the photovoltaic tin paste comprises the following steps:
[0099] S1. Place an organic solvent, rosin resin, organic acid activator and organic solvent in a reaction kettle with a heating device, heat to 100° C., and stir at a speed of 35 rpm for 8 min to make them uniform; add a thixotropic agent, a corrosion inhibitor and a surfactant to the above mixture, and after dissolving, stir at 30° C. and a speed of 20 rpm for 30 min, let it stand and cool, and after cooling for 24 hours, obtain the soldering flux;
[0100] S2. Mix the tin powder and the soldering flux, place in a mixer, evacuate, flush with nitrogen, and then stir at 30° C. and 12 rpm for 55 min to obtain the photovoltaic tin paste.
[0101] Example 4
[0102] This embodiment provides a photovoltaic tin paste, which is different from Embodiment 1 only in that the lead-free alloy tin powder does not contain silver, the copper content is increased to 2%, the tin content is 98%, and the other component contents and preparation methods are exactly the same as those in Embodiment 1.
[0103] Example 5
[0104] This embodiment provides a photovoltaic tin paste, which is different from Embodiment 1 only in that the lead-free alloy tin powder does not contain copper, the silver content is 2%, the tin content is 98%, and the other component contents and preparation methods are exactly the same as those in Embodiment 1.
[0105] Example 6
[0106] This embodiment provides a photovoltaic tin paste, which is different from the embodiment 1 only in that the organic solvent includes 20% propylene glycol and 20% ethanol, and the contents of other components and the preparation method are completely consistent with those of the embodiment 1.
[0107] Example 7
[0108] This embodiment provides a photovoltaic tin paste, which is different from the embodiment 1 only in that the organic acid includes 0.5% oxalic acid and 1.0% n-octanoic acid, and the contents of other components and the preparation method are completely consistent with those in the embodiment 1.
[0109] Example 8
[0110] This embodiment provides a photovoltaic tin paste, which is different from Example 1 only in that hydrogenated castor oil is replaced with ethylene bisstearamide of equal mass, and the contents of other components and the preparation method are exactly the same as those in Example 1.
[0111] Example 9
[0112] This embodiment provides a photovoltaic tin paste, which is different from the first embodiment only in that benzotriazole is replaced by ethylene glycol benzothiazole of equal mass, and the contents of other components and the preparation method are exactly the same as those in the first embodiment.
[0113] Example 10
[0114] This embodiment provides a photovoltaic tin paste, which is different from Example 1 only in that nonylphenol polyoxyethylene (10) ether is replaced by an equal mass of hexadecyltrimethylethylamine bromide, and the contents of other components and the preparation method are exactly the same as those in Example 1.
[0115] Embodiment 11
[0116] This embodiment provides a photovoltaic tin paste, which is different from Embodiment 1 only in that the modified rosin is replaced with water-white rosin of equal mass, and the contents of other components and the preparation method are completely consistent with those of Embodiment 1.
[0117] Example 12
[0118] This embodiment provides a photovoltaic solder paste, which is different from the embodiment 1 only in that the soldering flux is composed of the following components by mass percentage:
[0119]
[0120] The contents of other components and the preparation method are exactly the same as those in Example 1.
[0121] Example 13
[0122] This embodiment provides a photovoltaic solder paste, which is different from the embodiment 1 only in that the soldering flux is composed of the following components by mass percentage:
[0123]
[0124] The contents of other components and the preparation method are exactly the same as those in Example 1.
[0125] Comparative Example 1
[0126] This comparative example provides a photovoltaic tin paste, which is different from Example 1 only in that the photovoltaic tin paste is composed of the following components in terms of mass percentage: 80% lead-free alloy tin powder and 20% soldering flux, and the contents of other components and the preparation method are exactly the same as those in Example 1.
[0127] Comparative Example 2
[0128] This comparative example provides a photovoltaic tin paste, which is different from Example 1 only in that the photovoltaic tin paste is composed of the following components by mass percentage: 95% lead-free alloy tin powder and 5% soldering flux, and the contents of other components and the preparation method are exactly the same as those in Example 1.
[0129] Comparative Example 3
[0130] This comparative example provides a photovoltaic tin paste, which is different from Example 1 only in that the lead-free alloy tin powder is replaced with pure tin powder of equal mass, and the contents of other components and the preparation method are exactly the same as those in Example 1.
[0131] Comparative Example 4
[0132] This comparative example provides a photovoltaic tin paste, which is different from Example 1 only in that the modified rosin is replaced with pure rosin of equal mass, and the contents of other components and the preparation method are completely consistent with those of Example 1.
[0133] Application Example 1
[0134] This application example uses the photovoltaic tin paste provided in Example 1 to prepare two types of solar cells (P-type PREC cell and N-type Topcon cell);
[0135] IP type PREC battery cell (its structure is as follows Figure 1 (shown)
[0136] S1. Take the blue film before printing, print back silver and back aluminum on the back of the blue film, and dry it;
[0137] S2, printing the main grid and the sub-grid silver paste on the front side, printing the silver paste with a height of 2 μm, and then sintering it at a high temperature of 500°C to form an ohmic contact between the silver paste and silicon;
[0138] S3, printing the tin paste provided in Example 1 on the main grid silver paste surface on the front and back sides, and then baking at 250° C. for 40 seconds to solidify the tin paste and combine with the silver grid lines, and finally controlling the height of the main grid lines to be 12 μm, and completing the production of the battery cell;
[0139] After the battery cells are tested and graded, the components are manufactured. The component ends are normally welded to the main grid lines with solder strips (tin-coated copper strips). The silver of the main grid and the solder strip welding have a certain proportion of false soldering. The main grid surface of the battery cell manufactured by the present invention has a layer of tin paste. During welding, the tin on the main grid and the tin on the solder strip are dissolved and mixed together. After cooling, they can be better combined, reducing the proportion of false soldering.
[0140] II.N-type Topcon cell (its structure is as follows Figure 2 (shown)
[0141] S1. The blue film before printing, the main grid and the secondary grid silver paste are printed on the front and back, respectively, the printing height of the silver paste is 2μm, and then it is sintered at a high temperature of 500℃ to obtain a preliminary battery cell;
[0142] S2. Print the tin paste on the main grid silver paste surface on the front and back sides, and then bake at 250°C for 40 seconds to solidify the tin paste and combine with the silver grid lines. Finally, the height of the main grid lines is controlled at 12μm, and the battery cell production is completed.
[0143] Application Example 2
[0144] This application example uses the photovoltaic tin paste provided in Example 2 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 2.
[0145] Application Example 3
[0146] This application example uses the photovoltaic tin paste provided in Example 3 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 3.
[0147] Application Example 4
[0148] This application example uses the photovoltaic tin paste provided in Example 4 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 4.
[0149] Application Example 5
[0150] This application example uses the photovoltaic tin paste provided in Example 5 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 5.
[0151] Application Example 6
[0152] This application example uses the photovoltaic tin paste provided in Example 6 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 6.
[0153] Application Example 7
[0154] This application example uses the photovoltaic tin paste provided in Example 7 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 7.
[0155] Application Example 8
[0156] This application example uses the photovoltaic tin paste provided in Example 8 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 8.
[0157] Application Example 9
[0158] This application example uses the photovoltaic tin paste provided in Example 9 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 9.
[0159] Application Example 10
[0160] This application example uses the photovoltaic tin paste provided in Example 10 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 10.
[0161] Application Example 11
[0162] This application example uses the photovoltaic tin paste provided in Example 11 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 11.
[0163] Application Example 12
[0164] This application example uses the photovoltaic tin paste provided in Example 12 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 12.
[0165] Application Example 13
[0166] This application example uses the photovoltaic tin paste provided in Example 13 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Example 13.
[0167] Comparative application example 1
[0168] This application example uses the photovoltaic tin paste provided in comparative example 1 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of application example 1, except that the tin paste provided in embodiment 1 is replaced by the tin paste provided in comparative example 1.
[0169] Comparative Application Example 2
[0170] This application example uses the photovoltaic tin paste provided in comparative example 2 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of application example 1, except that the tin paste provided in example 1 is replaced by the tin paste provided in comparative example 2.
[0171] Comparative Application Example 3
[0172] This application example uses the photovoltaic tin paste provided in comparative example 3 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of application example 1, except that the tin paste provided in embodiment 1 is replaced by the tin paste provided in comparative example 3.
[0173] Comparative Application Example 4
[0174] This application example uses the photovoltaic tin paste provided in Comparative Example 4 to prepare two types of solar cells respectively, which is completely consistent with the preparation process flow of Application Example 1, except that the tin paste provided in Example 1 is replaced by the tin paste provided in Comparative Example 4.
[0175] Test Case
[0176] Test samples: solar cells prepared in application examples 1 to 13, and solar cells prepared in comparative application examples 1 to 4;
[0177] (1) Welding test: After curing, weld at 250℃. After being kept still for 5 minutes at room temperature, use a tensile tester to test the welding tensile force, and calculate the welding pass rate (the pass rate is the number of pad points with welding tensile force ≥1.5N, and the proportion of the total number of pad points). The tensile force refers to the adhesion between the solder strip and the slurry, and between the slurry and the silicon wafer surface. The magnitude of the tensile force affects the physical series / parallel connection performance of the components composed of the final silicon wafer.
[0178] (2) Fill factor and conversion efficiency test: Use an IV tester to test the fill factor and conversion efficiency. FF refers to the fill factor, and Eta refers to the cell conversion efficiency; the degree of contact between the slurry and the silicon wafer. The higher the contact, the higher the efficiency, but it will affect the adhesion between the slurry and the silicon wafer, resulting in a decrease in the pulling force.
[0179] The test results of PERC cells are shown in Table 1 below:
[0180] Table 1
[0181]
[0182]
[0183] The test results of Topcon cells are shown in Table 2 below:
[0184] Table 2
[0185]
[0186] As shown in Tables 1 and 2 above, the tin paste of the present invention can be directly printed on the screen and covered on the surface of the underlying silver paste. After baking and curing, the tin paste and the silver grid are firmly combined together without the need for cleaning. This not only plays a conductive role, but also improves the soldering yield of the component end.
[0187] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A photovoltaic tin paste, characterized in that: The photovoltaic tin paste comprises, by weight: 85-90 parts of lead-free alloy tin powder and 10-15 parts of flux; The soldering flux comprises, by mass percentage, 30-50% of an organic solvent, 1.0-2.0% of an organic acid, 0.5-2.5% of a thixotropic agent, 0.8-1.5% of a corrosion inhibitor, 1.0-3.0% of a surfactant, and the remainder is modified rosin; The organic solvent is selected from any one or a combination of at least two of propylene glycol, diethylene glycol monobutyl ether, ethylene glycol methyl ether, isopropyl alcohol, methyl silicate, ethylene glycol or dodecyl alcohol; The organic acid is selected from any one or a combination of at least two of succinic acid, sebacic acid, phthalic acid, dodecanoic acid, tetradecanoic acid or hexadecanoic acid; The thixotropic agent is selected from any one or a combination of at least two of hydrogenated castor oil, polyamide wax, organic bentonite or silicon dioxide; The corrosion inhibitor is selected from any one of hydroquinone, benzotriazole or toluene triazole or a combination of at least two thereof; The surfactant is selected from any one or a combination of at least two of nonylphenol polyoxyethylene (10) ether, octylphenol polyoxyethylene (10) ether or polyoxyethylene fatty acid ester; The modified rosin includes any one or a combination of at least two of the following compounds:
2. The photovoltaic tin paste according to claim 1, characterized in that: The lead-free alloy tin powder comprises, by mass percentage, 0-3.0% silver, 0.5-2.0% copper, and the balance tin.
3. A method for preparing a photovoltaic tin paste according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: The organic solvent, organic acid and modified rosin are mixed for the first time, and then a thixotropic agent, a corrosion inhibitor and a surfactant are added and mixed for the second time to obtain the soldering flux; The lead-free alloy tin powder and the soldering flux are mixed for a third time to obtain the photovoltaic tin paste.
4. The method for preparing photovoltaic tin paste according to claim 3, characterized in that: The temperature of the first mixing is 80-120° C.; the stirring speed of the first mixing is 30-40 rpm; and the time of the first mixing is 5-10 min.
5. The method for preparing photovoltaic tin paste according to claim 3, characterized in that: The temperature of the second mixing is 30-50° C.; the stirring speed of the second mixing is 20-25 rpm; and the time of the second mixing is 20-40 min.
6. The method for preparing photovoltaic tin paste according to claim 3, characterized in that: The temperature of the third mixing is 30-50° C.; the stirring speed of the third mixing is 10-15 rpm; and the time of the third mixing is 30-60 min.
7. A solar cell, characterized in that: The main grid of the solar cell comprises a silver grid line and a tin paste layer; Wherein, the tin paste layer covers the surface of the silver grid line, and the tin paste layer is formed by curing the photovoltaic tin paste as described in claim 1 or 2.
8. The solar cell according to claim 7, characterized in that: The solar cell comprises a P-type PREC cell or an N-type Topcon cell.
9. The solar cell according to claim 7, characterized in that: The height of the silver grid line is 1-3 μm.
10. The solar cell according to claim 7, characterized in that: The height of the tin paste layer is 7-14 μm.
11. A method for preparing a P-type PREC cell, characterized in that: The method for preparing the P-type PREC cell comprises the following steps: Print back silver and back aluminum on the back of the blue film and dry it; Print the silver main grid on the front of the blue film and sinter it; The photovoltaic tin paste as claimed in claim 1 or 2 is printed on the surface of the back silver and the silver main grid respectively, and then cured to obtain the P-type PREC cell.
12. A method for preparing an N-type Topcon cell, characterized in that: The method for preparing the N-type Topcon cell comprises the following steps: Print silver main grids on the front and back of the blue film and sinter them; The photovoltaic tin paste as claimed in claim 1 or 2 is printed on the surface of the silver main grid on the front and back sides respectively, and then cured to obtain the N-type Topcon cell.
Citation Information
Patent Citations
Photovoltaic cell and method for preparing grid electrode of photovoltaic cell through reflow soldering process
CN114346348A
Lead-free and halogen-free solder paste
US11992901B1